PSYCHIATRIC ASPECTS OF LONG: TERM CARE - Ira Aini Dania (JURNAL KESMAS DAN GIZI (JKG), 2019)
The emergence of nursing homes in the Middle Ages has introduced health programs specifically health care which occupy the largest proportion of nursing homes services. Nursing homes provide services, medical care, for injury problems, disability in sick patients and need services and medical care and rehabilitation. Many nursing providers provide good care, but in many other countries it guarantees nursing homes to individuals who are cared for but they are very inadequate, sometimes very surprising, the services provided actually accelerate their physical, mental, and emotional health deterioration. They often get rights violations and are even subject to physical abuse. This article discusses matters relating to history and psychiatric services for those who have become nursing home residents since 1990.